The Turnaround of the Swedish Economy : Lessons from Large Business Sector Reforms - Heyman, Fredrik; Norback, Pehr-Johan; Persson, Lars (Published by Oxford University Press on behalf of the World Bank, 2021)
How can a country improve productivity growth in its business sector and reach its growth potential? Sweden during the 1970–2010 period can serve as an example to help other countries understand how to efficiently reform a business sector. In the 1990s, Sweden implemented a reform package that ignited a successful reorganization of a business sector that had faltered for decades. To understand the economic forces behind this process, the paper first surveys the industrial restructuring literature and then examine the reform package using Swedish matched plant-firm-worker data. The removal of barriers to growth for new and productive firms, as well as increased rewards for investment in human capital, were crucial to the success of Sweden's reforms. The paper also discusses how the reform experience of a developed country such as Sweden can be useful for developing countries that are in the process of transforming their business sectors. The findings suggest that policymakers have much to learn from country case studies and that the Swedish experience can be a valuable case study for developing countries that are attempting to promote growth by developing their business sectors.